An investigation in to the forecasting practices in Malaysian electronics industry [microfilm] - Maizah Ahmad (Skudai : Universiti Teknologi Malaysia, 2000)
Thesis (Doctor of Philosophy) - Universiti Teknologi Malaysia, 2000